Different Heat Shock Application Effect on Gynogenetic Production of Zebrafish (Danio Rerio) - Ozdemir, Rahmi Can; Ekici, Aygül (OMICS Publishing Group, 2017)
The present study aimed to obtain gynogenetic zebrafish. For this purpose, zebrafish spermatozoa exposed to UV irradiation to make it haploid gynogenetic fish and heat shock was applied to haploid zygote in order to obtain gynogenetic diploid fish. Temperature, which is an important factor of the production, is taken into consideration in this study. In this respect, this study compared the results of 41.4°C and 41°C heat-shock applications and found that 12nd-24th-48th-72nd hour survival rate was maximum at 41,4°C (P<0.05). When considered from hatching rate (72th-78th hour) view at 41.4°C was 17.3 ± 3% in gynogenetic diploid group and heat-shock application at 41°C survival rate was 14 ± 2% in gynogenetic diploid group and there is no survivor in haploid group, was observed (P<0.05). The result of the karyotype analysis in haploid gynogenetic embryos, ruptured chromosome fragments was identified. Also in karyotype analysis of diploid gynogenetic embryos, 2n=50 chromosomes was identified. On 3rd day after fertilization, total body length of the haploid gynogenetic fish was 39.6% shorter and body thickness was 33% thicker than the diploid gynogenetic group. Our gynogenetic fish producing method and the different heat-shock applications improved survival rate of gynogenetic fish.
Keywords: [SDV] Life Sciences [q-bio]; 14. Life underwater